أثر تفريق الخطابي بين النعت والصفة في ترتيبه لوجوه الإعجاز في رسالته: "بيان إعجاز القرآن": (The Impact of Al-Khattabi’s Distinction between Attribute (Naʿt) and Description (Ṣifah) in His Treatise ‘Bayān Iʿjāz al-Qurʾān’) - هبة مجد الدين صباهي; محمد عبد اللطيف (At-Tajdid - Intellectual Refereed Journal, 2024)
Abstract This study focuses on examining the impact of Al-Khattabi’s distinction between the terms "attribute" (sifah) and "description" (na’t) in his arrangement of the aspects of the Qur’an’s miraculous nature, as mentioned in his treatise "The Exposition of the Qur’an’s Miraculous Nature." The study employs both the inductive method and the analytical method. It includes a definition of Imam Al-Khattabi and his treatise, an explanation of the meanings of the terms "attribute" and "description," the distinction made by grammarians between them, and the rationale behind Al-Khattabi’s differentiation between these terms, despite neither term appearing in the Qur’an. This differentiation is maintained by referencing Qur’anic terms to explain the distinction and its impact on his discussion of the aspects of the Qur’an’s miraculous nature mentioned in his treatise. One of the key findings of the study is that Al-Khattabi’s choice to differentiate between "attribute" and "description" had a clear objective, reflected in his arrangement of the aspects of the Qur’an’s miraculous nature, his description of them, and the appropriate space given to each aspect in his treatise. He identified the first aspect as the motive to imitate the Qur’an, calling it the "convincing aspect," and the second aspect as the theory of inimitability, calling it the "approachable aspect." These two aspects pertain to the audience and are not intrinsic to the Qur’an, meaning they are not descriptions of it. The third aspect is foretelling future events, but it is not universal since it does not apply to all verses and surahs, meaning it is not a description of the Qur’an. However, he called the aspect of eloquence "intrinsically desirable," indicating it is an attribute of the Qur’an, unlike the fifth aspect: its effect on souls, as this is known only to a few individuals. Furthermore, Al-Khattabi’s use of the term "description" to explain the aspects of inimitability and foretelling the unseen confirms that these aspects can be detached from the Qur’an in certain contexts, as evidenced by his commentary on these aspects. Keywords: Qur’an, Al-Khattabi, Miraculous Nature, Attribute, Description.